If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(10 + 2x) = 30 (10 * 3 + 2x * 3) = 30 (30 + 6x) = 30 Add '-30' to each side of the equation. 30 + -30 + 6x = 30 + -30 Combine like terms: 30 + -30 = 0 0 + 6x = 30 + -30 6x = 30 + -30 Combine like terms: 30 + -30 = 0 6x = 0 Solving 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 0 Simplifying x = 0
| 7x-21y=84 | | b-3=-2 | | 3(8-4x)=-60 | | x+5y=14 | | 4(2x-4)-3(x-2)=-2(4x+15) | | 2x^2+5x-0.33=0 | | -4a=-24 | | 5-4y-y=-29 | | 5+z=5 | | -3x+6=31+2x | | 2y+3x=10 | | 2x^2+13x+15= | | 2x^2+5x-0.66=0 | | 7(-3x+4)= | | -24=6-15-5a | | 2x-y=-15 | | -3y+2=-4 | | R+3=17 | | -7x+9=-4x-3 | | 23x-16=14-7x | | x^2+x^2+9=89 | | x+9=-36+6x | | 4+3x=7x+4 | | 7y=-28+7 | | 5x(3x+8)=4 | | 3x+7=12+4x | | 6x-5=3+5x | | x(x+3)-2=2+x(x+1) | | y=x^2+2x-15 | | 3x+2=3x+56 | | 9x=9y-18 | | (40x^2-13x+1)=0 |